Empirical validation of the psychological concept of a perceived feeling of ‘energy’: Advancement into the study of positive psychology - Huy P. Phan (Public Library of Science (PLoS), 2021)
The paradigm of positive psychology, significant in nature, helps to explain the proactivity and motivation of human agency, such as a secondary school student’s state of autonomy, confidence, and personal resolve to strive for optimal learning and/or non-learning experiences. Our recent research development, in tandem with other scholars’ inquiries, has focused on one aspect of positive psychology–namely, a person’s achievement of ‘optimal best’, which reflects the maximization of his/her state of functioning (e.g., cognitive functioning). Capitalizing on our previous research, we develop a psychological concept that we term as a ‘perceived feeling of energy’. A perceived feeling of energy (e.g., a perceived feeling of liveliness) is proposed to act as a ‘motivational engine’, or as a central driver, which then could predict and enhance a person’s achievement of optimal best. Six hundred and twenty-seven university students (N = 438 women, 189 men) responded to a suite of self-report questionnaires. Structural equation modelling (SEM) techniques were used to test a conceptual model, where we focused on the antecedent (i.e., the direct impact of self-efficacy on a perceived feeling of energy) and consequence of a perceived feeling energy (i.e., the impact of a perceived feeling of energy on personal resolve, and the sustaining of optimal best). Analysis of results showed support for our original hypothesized model–for example: self-efficacy as an antecedent of energy and the central role of the energy as a predictor and potential mediator of future outcomes.